(3GdeMGSHI GdEOGQjI hGdSjGSGJ GdEOGQjI GdeYGUQIs - (3jhMfG (B, (3Bd BOes; (3UGdM GdQRb(B, s ((3YeGf(B:s (3OGQ GdMGeO ddfTQ hGdJhRjY,s, 2006)
(3jVe GdeMGSHI GdEOGQjI hfXe GdeYdheGJ, UfY GdbQGQGJ GdGOGQjI, GdeMGSHI GdGOGQjI hHQGeL GdJNWjW, GdeMGSHI GdGOGQjI hJbjje GdCOGA(B.s
(3HjHdjhZQGajG(B: (3U(B.555(3; edGMb(B: (3U(B.559s
Keywords: (3GdJNWjWs; (3GdeMGSHI GdEOGQjIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s